THE COPPING STRATEGIES IN REDUCING ANXIETY WHILE TEACHING EYL - Yuliani, Mustika; Sintu, Gabriella Maria Mancelina; Yugafiati, Rasi (IKIP Siliwangi, 2019)
Teaching English for Young Learner is not easy for several students. They face the obstacles in applying the science of pedagogy for Young Learners. The also have barriers to interact with children. However the teaching learning process may enjoyable if both of teachers and learners get fun together. This research examines what obstacles faced by several students when teaching English for Young Learners. This study also aims to explore the phenomenon of how reducing these anxiety. This research uses descriptive qualitative. There are seven persons as participants in this research. The result shows that they feel dizzy, anxious, and various other anxiety symptoms. They are anxious about lack of focus of young learners, mispronounce, inappropriate action, and unruly learners. The copping strategies are : prepare and understand the material correctly, find out students’ characteristics, take a breath, and drink. They reduce the anxiety while teaching English for young learners with well prepare and the result are tranquility, believe, and pleasures. Keywords: copping strategies, reducing anxiety, teaching EYL